Uporaba konfokalne laserske mikroskopije za ugotavljanje poroznosti naravnega kamna na primeru kalcitnega marmorja - Mauko, Alenka (Geologija, 2008)
Porosity is one of the key characteristics of natural stone, which influencesondurabilityaswellasfunctionality of stone as building material. Further, deterioration processes themselves are also characterized by change of porosity. Different direct and indirect techniques can be used for porositydetermination. In the following paper overview of these methods, as well as their advantages and disadvantages, is given. Confocal laser scanning microscopy (CLSM) is indirect (microscopic) technique. Despite its numerous advantages, among which 3D visualization of pore structure is of major importance, this technique is less known in the area of building materials. Anexample how CLSM can be applied for qualitative and quantitative evaluation of porosity of calcitic polygonal granoblastic marble is given in this paper. Studied marble has been, despite of its poor durability, often used as building material, especially in the case of claddings. It is shown that thermal hydric factors of deterioration can influenceporositysignificantly,especiallyformationofintergranularcracks.Thiskin dofdeteriorationcanbesuccessfully evaluated with use of CLSM method, if samples are suitable prepared and if suitable image analysis tools are developed.
Keywords: gradbeni materiali; laserska tehnika; marble; marmor; mikroskopiranje; naravni kamni; porozni materiali